EFFECT OF EMS ON ANTIOXIDANT ENZYME ACTIVITY AND OXIDATIVE STRESS OF TRITICUM AESTIVUM L. VAR HD-2894 - Dubey, Shailja; Bist, Renu; Misra, Shrilekha (International Journal of Current Pharmaceutical Research, 2018)
Objective: Ethyl methano sulphonate (Ems), a chemical mutagen is widely used to induce a large number of functional variation in wheat plant. The objective of present study was to determine the activity of enzymatic antioxidants and Lipid peroxidation (LPO) after EMS exposure in a wheat plant in M1, M2 and M3 generation of Triticum aestivum L. var. HD 2894. Methods: Presoaked seeds were treated with EMS for 6 hour with different concentration like 0%, 0.1%, 0.2%, 0.3%, 0.4% and 0.5%. Some biochemical parameter such as Catalase (CAT), ascorbate peroxidase (APX), glutathione reductase (GR) and Lipid peroxidation (LPO) were studied. Results: Our result showed that EMS affects enzymatic and oxidative parameters in all generation. CAT, GR, APX and LPO activity was found to be reduced in m1 generation as compared to control. A simultaneous elevation was recorded in the concentration of ems compared to control treated plants after given the exposure of ems in m2 and m3 generation. Data analysis of antioxidant and LPO during the m2 generation showed that the effect of the mutagen on the activity of antioxidant and LPO did not cease in the m1 but continued to affect the m2 generation. Analysis of m3 generation showed stability in the activity of antioxidant and LPO from m2 to m3 generation. Conclusion: Lethal dose of ems was determined by the activity of antioxidant under laboratory condition. In this experiment, quantitative determination was applied as a regular procedure. The data analysis showed the activity of antioxidant, LPO and doses of ems concentration in m1, m2 and m3 generation. Variability observed on the basis of mean and standard deviation. On the whole, differences between concentrations and treatment time of Ems significantly affect the activity of antioxidant and LPO in all generation. Â 